2022
DOI: 10.1039/d1nr06131c
|View full text |Cite
|
Sign up to set email alerts
|

Emerging low-molecular weight nucleopeptide-based hydrogels: state of the art, applications, challenges and perspectives

Abstract: Over the last twenty years, low-molecular weight gelators and, in particular, peptide-based hydrogels, have drawn great attention of scientists thanks to both their inherent advantages in terms of properties and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 109 publications
1
25
0
Order By: Relevance
“…The higher peptide yield indicated that the hydrolysis was more effective, thereby more peptides with lower molecular weight were formed. Numerous studies have reported that the peptides with lower molecular weight exhibited stronger bioactivity as compared with proteins. , Moreover, our preliminary in vitro experiments have confirmed that there was an inverse relationship between the molecular weight and the activity of the peptides. Thus, in this study, the yield and molecular weight of the peptides were chosen to be indicators as the preparation of Se-EWP.…”
Section: Resultssupporting
confidence: 74%
“…The higher peptide yield indicated that the hydrolysis was more effective, thereby more peptides with lower molecular weight were formed. Numerous studies have reported that the peptides with lower molecular weight exhibited stronger bioactivity as compared with proteins. , Moreover, our preliminary in vitro experiments have confirmed that there was an inverse relationship between the molecular weight and the activity of the peptides. Thus, in this study, the yield and molecular weight of the peptides were chosen to be indicators as the preparation of Se-EWP.…”
Section: Resultssupporting
confidence: 74%
“…The nucleobase-bearing short peptide-based supramolecular structures have natural ability to self-assemble via non-covalent interactions. Supramolecular hydrogels offer specific benefits, such as modularity, tunability, bottom-up design, extracellular matrix-like structure, biomimicry, responsiveness to physical, mechanical, chemical or biological stimuli ( Scognamiglio et al, 2021 ; Giraud et al, 2022 ). Hence, they are suitable for inter alia drug delivery ( Noblett et al, 2021 ).…”
Section: Landscape Of Opportunities: Topical Insightsmentioning
confidence: 99%
“…Hence, they are suitable for inter alia drug delivery ( Noblett et al, 2021 ). Other innovative applications of nucleopeptides will appear in the next years, due to their appealing features such as reduced cytotoxicity or precise control of the properties ( Giraud et al, 2022 ).…”
Section: Landscape Of Opportunities: Topical Insightsmentioning
confidence: 99%
“…But the problem of finding this line remains difficult, especially when one is dealing with a nitrogen atom embedded in an environment that is not fully rigid. This is precisely the problem addressed here in hydrogels formed by nucleobase-containing peptides (also termed nucleopeptides) . In such hydrogels, it may happen that a given NH grouping of a nucleobase is partly immobilized and then able to produce NQR peaks at unpredictable frequencies due to the labile character of the NH grouping.…”
Section: Introductionmentioning
confidence: 98%